Optimalisasi Three Point of Lighting pada Program Feature Warisan Budaya â€œTari Topeng Panca Wanda Penuh Maknaâ€ - Sari, Chintya Intan Permata; Kristiadi, David (Jurnal Ilmiah Multimedia dan Komunikasi, 2022)
Lighting is one of the important elements in a video production. However, lighting elements are often constrained by the limited number of tools, electricity sourcesavailability, conditions at the production location, as well as the production crew. These limitations become a challenge in the production of feature â€œWarisan Budayaâ€ Episode of â€œTari Topeng Panca Wanda Penuh Maknaâ€.The optimization of three points of lighting became the main idea in the lighting arrangement of this feature production. The production equipped the lighting with lamp type YONGNUO YN-600 LED, and applied the concept of Three Points of Lighting.Â  The selection of lamps and the lighting concept aims to create appropriate lighting, so as to create a spatial dimension. The results of the optimization of Three Points of Lighting and the use of the right equipments create dimensions of space in each scene of the work.